Food safety : innovative analytical tools for safety assessment - Spizzirri, Umile Gianfranco; Cirillo, Giuseppe, 1980- (Insights into modern food science., 2016)
Food safety and quality are key objectives for food scientists and industries all over the world. To achieve this goal, several analytical techniques (based on both destructive detection and nondestructive detection) have been proposed to fit the government regulations. The book aims to cover all the analytical aspects of the food quality and safety assessment. For this purpose, the volume describes the most relevant techniques employed for the determination of the major food components (e.g. protein, polysaccharides, lipds, vitamins, etc.), with peculiar attention to the recent development in the field. Furthermore, the evaluation of the risk associated with food consumption is performed by exploring the recent advances in the detection of the key food contaminants (e.g. biogenic amines, pesticides, toxins, etc.). Chapters tackle such subject as: -GMO Analysis Methods in Food -Current Analytical Techniques for the Analysis of Food Lipids -Analytical Methods for the Analysis of Sweeteners in Food -Analytical Methods for Pesticides Detection in Foodstuffs -Food and Viral Contamination -Application of Biosensors to Food Analysis. - Resumé vydavatel